An analysis of drought conditions in Central Vietnam during 1961-2007 - Hang, Vu Thanh; Trang, Nguyen Thi (VNU Journal of Science: Earth and Environmental Sciences, 2010)
Abstract . Monthly rainfall data given by surface meteorological observations during the period 1961-2007 in Central Vietnam is used to calculate drought indices. Results show that drought conditions slightly increase in North Central Vietnam but decrease in South Central and Highland Central Vietnam. Significant drought periods often occur from January to March. The percentage of dry years during the period 1961-2007 is larger than that in the reference period of 1961-1990 in North Central while smaller in South Central and almost similar to that in Highland Central Vietnam. Keywords :  Drought, trend, Central Vietnam.